Impacts of Blended Learning on Students’ Learning Motivation and Attitudes: A Case Study of Vietnamese EFL Students - Luu, Quy Khuong; Luu, Ngoc Bao Trang (International Journal of Educational Innovation and Research, 2024)
This study investigates the impacts of Blended Learning (BL) on Vietnamese EFL students' motivation and attitudes. It aims to determine whether BL instruction can enhance these aspects of language learning compared to traditional methods. A quasi-experimental design was used with 100 fourth-year EFL students divided into control and experimental groups. The experimental group received BL instruction with online materials and LMS support, while the control group received traditional face-to-face instruction. Both groups completed surveys measuring motivation and attitudes before and after the semester. The findings suggest that BL can improve EFL students' motivation and attitudes. The experimental group showed a statistically significant increase in motivation compared to the control group. Students in the BL class report a stronger desire for self-directed learning and enjoyment in the classes. The study also explores limitations and future research directions, including sample size, short-term impact, and comparative studies.